Disease Modeling in Stem Cell-Derived 3D Organoid Systems. Issue 5 (May 2017) - Dutta, Devanjali; Heo, Inha; Clevers, Hans
Abstract : Organoids are 3D in vitro culture systems derived from self-organizing stem cells. They can recapitulate the in vivo architecture, functionality, and genetic signature of original tissues. Thus, organoid technology has been rapidly applied to understanding stem cell biology, organogenesis, and various human pathologies. The recent development of human patient-derived organoids has enabled disease modeling with precision, highlighting their great potential in biomedical applications, translational medicine, and personalized therapy. In light of recent breakthroughs using organoids, it is only apt that we appreciate the advantages and shortcomings of this technology to exploit its full potential. We discuss recent advances in the application of organoids in studying cancer and hereditary diseases, as well as in the examination of host cell–microorganism interactions. Trends: Organoids can be developed from pluripotent stem cells and adult stem cells. Organoids have been established for multiple organs including intestine, kidney, brain, liver, stomach, pancreas, ovary, and lung. Organoids can be used in multiple clinical applications including disease modeling, drug screening, host–microbe interactions, and regenerative therapy. Patient-derived organoids may enable personalized medicine. Genes can be manipulated within organoids using molecular technologies such as the lentiviral expression system and CRISPR/Cas9; this may enable disease modeling and targeted gene therapy. The complex interplay between microbes – bacteria, parasites, and viruses – and the host epithelium have been dissected using organoids derived from brain, stomach, and intestine. Mechanically dynamic designer matrices such as hybrid polyethylene glycol hydrogels might expand the applicability of organoids in the future.